Prevalence, correlates, and comorbidities of internet gaming disorder and problematic game use: national mental health survey of Korea 2021 - Ko, Young-Mi; Lee, Eun Sol; Park, Subin (Frontiers in Psychiatry, 2024)
Background This study investigated the prevalence, correlates, and comorbidities of Internet Gaming Disorder and problematic game use among the general population in Korea. Methods The data of 2,764 individuals aged 18 to 49 years who participated in the National Mental Health Survey of Korea 2021 were analyzed. The diagnostic assessments were based on the Structured Clinical Interview for Internet Gaming Disorder and the Composite International Diagnostic Interview. The Game Overuse Screening Questionnaire assessed problematic game use. Multiple logistic regression analyses were performed, and a complex sampling design analysis was applied. Results The 12-month prevalence rate of Internet gaming disorder (IGD) was 0.8% and the 1-month prevalence rate of problematic game use was 8.4%. IGD was higher in men, younger people, unemployed, and in those with low physical activity, dissatisfaction with their quality of life, and who perceived more loneliness and social isolation. While both alcohol use disorder (AUD) and Attention-Deficit/Hyperactivity Disorder (ADHD) were significantly associated with IGD, only ADHD was significantly associated with problematic game use. Conclusion IGD and problematic game use are relatively prevalent in the Korean adult population and are comorbid with AUD and ADHD. Therefore, a preventive strategy for IGD and problematic game use is needed for game users who are more likely to be addicted, such as younger male users. In addition, mental health screening and appropriate treatment for both game addiction and comorbid psychiatric disorders should be provided to individuals with IGD and problematic game use.